The principles of equity & trusts - Virgo, Graham (Oxford University Press, 2012)
The Principle of Equity and Trusts offers students a new approach to this dynamic area of law. Professor Graham Virgo has created a rigorous yet accessible student companion which draws the field in its contemporary context, offering a critical and insightful commentary on the law, its application, and development